Analysis of Income Distribution among Goat Farmer Households in Banjarnegara District, Central Java Province Indonesia - Sugiarto, Moch; Ahmad, Abdul Aziz (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
The objective of this study was to describe the structure of householdâs income of goat farmer and analyze the distribution of goat farmer householdâs income in Banjarnegara. For this analysis, Banjarnegara district was divided into three agro ecological zones on the basis of altitude, i.e. low, medium and high land. 180 goat farmers were selected using multistage sampling and data were measured using descriptive statistic and Gini Coefficient. The study concluded that goat farming as a side job contributed 29% of total household income. The income from non-goat farming remain dominating a structure of household income by 71%. There was a high inequality household income among goat farmers with Gini Coefficient of 0.562. The high level of total income inequality was due to a greater relative inequality in non-goat farming income. Since there was a relationship between farm size and income, increasing the number of goats must be actualized to the goat farmers with no other livelihood. This would be able to reduce inequality of total income of goat farmers.